THE PROBLEM OF RADICALISM IN PROCESSES RELATED TO IDEOLOGICAL AND SPIRITUAL THREATS (Scientific journal of the Fergana State University, 2024)
The article will talk about the problem of radicalization in globalization and ideological processes, its internal semantic content. The place of ideology and its characteristic features are revealed in globalization. Ideology is the foundation on which terrorist activitiyes are built, reflecting its purposeful and value-semantic sides.